Perlocutionary Act In Black Panther Movie Script - Udiarni Zahada; Nur Israfyan Sofyan (ELITE: Journal of English Language and Literature, 2021)
This study tries to find out the use of perlocutionary acts in the Black Panther movie script, that is, how the characters’ utterances have some particular effects on other characters. The objective of this study is to describe the type of perlocutionary act which is used in the Black Panther movie script. This study uses a qualitative descriptive design. The source of data is obtained from the Black Panther movie script containing the dialog script of the characters’ utterances. The data are collected by reading the script intensively, watching the movie several times, and identifying, selecting, and coding the data. The data are analyzed by presenting the data, describing the data, interpreting the data, and concluding the data. The results show that the four types of the perlocutionary act which is used in the Black Panther movie script can be concluded based on the speakers’ communicative act purpose that can be either understood completely or can also be misunderstood by the interlocutor. The misunderstanding feedback of the interlocutors could be seen either in not realizing or not understanding the speakers’ utterances, the interlocutors intentionally tell lies or intentionally do not want to cooperate with the hearers, or the utterances’ meaning is clarified by the third speaker.